Rusʹ restored: selected writings of Meletij Smotrycʹkyj ; 1610 - 1630 - Smotrycʹkyj, Meletij (Harvard library of early Ukrainian literature / English translations, 2005)
Thrēnos (1610) -- Homiliary gospel (1616) -- Church Slavonic grammar (1618-1619) -- A funeral sermon (1621) -- A verification of innocence (1621) -- A defense of the "Verification" (1621) -- A refutation of acrimonious writings (1622) -- A justification of innocence (1623) -- Five letters (1627-1628) -- Apology (1628) -- A revocation (1628) -- A protestation (1628) -- Paraenesis (1629) -- Exaethesis (1629) -- A final letter (1630)